RUMUSAN DELIK DAN FORMULASI KETENTUAN PIDANA KHAMAR PADA QANUN ACEH NOMOR 6 TAHUN 2014 DALAM PERSPEKTIF KEBIJAKAN HUKUM PIDANA - Khairilina Khairilina (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
The formulation of a criminal should rely on appropriate criminal lawprinciples and policies. For example, about the type of punishment and criteria ofthe offender. In Qanun Aceh Number 6 of 2014, some formulations of criminalprovisions are distinguished between hudud and ta'zir punishments. Thisdistinction of punishment is based on direct-performers (drinkers of khamar) andnon-direct performers such as; providers, producers, sellers, promoters, and deedsparticipate in other khamar fingers. A legislation made by the government withthe legislature is always expected to give a sense of justice in society. This senseof justice is one of the goals of a legislation and punishment, in addition to otherobjectives of legal certainty and expediency. justice must be positioned as anabsolute state that must be realized by the law. But behind the hope of justice isoften also a complicated issue, sometimes the result of a legislative productactually creates imbalances in society. For that reason, the formulation of qanunand / or legislation should pay attention to criminal law policy